2005
DOI: 10.1351/pac200577122047
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in Lewis acid-Lewis base bifunctional asymmetric catalysis

Abstract: Two enantioselective cyanation reactions, the Strecker reaction of ketoimines and the Reissert reaction of pyridine derivatives, promoted by Lewis acid-Lewis base bifunctional asymmetric catalysts are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 10 publications
(10 reference statements)
0
16
0
2
Order By: Relevance
“…[372] Shibasaki and co-workers have demonstrated that the addition of TMSCN to fluorenylimines can be effected in the presence of catalyst 330 (Table 12). [373] However, these reactions were extremely sluggish, requiring days to reach high conversion (entry 1).…”
Section: Silylcyanation Revisited: N-s* Lewis Base-lewis Acid Catalysismentioning
confidence: 99%
“…[372] Shibasaki and co-workers have demonstrated that the addition of TMSCN to fluorenylimines can be effected in the presence of catalyst 330 (Table 12). [373] However, these reactions were extremely sluggish, requiring days to reach high conversion (entry 1).…”
Section: Silylcyanation Revisited: N-s* Lewis Base-lewis Acid Catalysismentioning
confidence: 99%
“…[372] Shibasaki und Mitarbeiter berichteten Schema 112]. [378] Für die asymmetrische Cyanosilylierung von Aldehyden wurde eine Reihe sehr ähnlicher Systeme beschrieben, die sowohl Lewis-saure als auch Lewis-basische Gruppen enthalten [Gl.…”
Section: Asymmetrische Alkylierungen Mit Diethylzinkunclassified
“…In general, two types of activation modes exist for catalytic nucleophilic addition reactions: (1) activation of nucleophile precursors by basic catalysts to abstract their acidic portions, such as α-hydrogen atoms, and (2) lowering the LUMO levels of electrophiles by interaction with Brønsted or Lewis acidic catalysts. Thus, the ideal pathway for nucleophilic reactions is dual activation of both electrophiles and nucleophiles by acidic and basic catalysts, respectively (Scheme 1) 1), 2) . However, the existence of both strongly acidic and basic species in solution induces neutralization resulting in inactive salts.…”
Section: Introductionmentioning
confidence: 99%
“…Later reports described, several bifunctional catalysts with both an organic acid and base used for carbon _ carbon bond-forming reactions 8) 11) . For type (2) catalysts, the silanol group on the silica surface was reported as a weak acid site for the promotion of amineor NH2 group-catalyzed reactions 12), 13) . In 2003, Kubota and co-workers reported that silanol groups on SiO2 significantly enhanced amine-catalyzed aldol reactions 14) .…”
Section: Introductionmentioning
confidence: 99%